Nasal Gel Loaded with Amphotericin Nanotransferosomes as Antifungal Treatment for Fungal Sinusitis - Khaled M. Hosny; Nabil A. Alhakamy (MDPI AG, 2020)
On the basis of fungal involvement, rhinosinusitis is categorized into allergic, mycetoma, chronic, and acute invasive types. The aim of the current study was to evaluate the efficacy of an amphotericin gel in situ loaded with nanotransferosomes against Aspergillus flavus, which causes allergic rhinosinusitis. A Box-Behnken design was utilized to study the interaction among the nanotransferosomes and optimize independent variables in formulating them, in order to match the prerequisites of selected responses. The optimal formulation was determined to be 300 mg/mL soybean lecithin, 200 mg/mL amphotericin B (AMP), and 150 mg/mL clove oil, resulting in a particle size of 155.09 nm, 84.30% entrapment efficacy (EE), inhibition zone of 16.0 mm, and 0.1197 mmol serum creatinine. The optimized batch was further prepared into an in situ gel and evaluated for various parameters. The optimized formulation released 79.25% AMP and enhanced permeation through the nasal membrane, while the other formulations did not achieve complete absorption. According to in vivo tests using rabbits as animal models, the optimized AMP-nanotransferosomal formulations (NT) in in situ gel result in a non-significant difference among the various kidney function parameters. In conclusion, nasal in situ gel loaded with AMP-clove oil nanotreansfersomes can act as a promising novel carrier that enhances antifungal activity and decreases AMP nephrotoxicity.